2016
DOI: 10.1016/j.molcata.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

OH-substituted tridentate ONO Schiff base ligands and related molybdenum(VI) complexes for solvent-free (ep)oxidation catalysis with TBHP as oxidant

Abstract: Molybdenum complexes with ONO tridentate Schiff base ligands based on salicylideneaminophenolato (SAP) backbone with OH substitution on the salicyl arene ring have been synthesized and characterized. The molecular structures of the full series of OH substituted molybdenum complexes were determined by X-ray crystallography as monomers stabilized by one solvent molecule, [MoO2L(D)]. All dimeric complexes [MoO2L]2 were tested for the epoxidation of cyclooctene and cyclohexene under organic solvent-free conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…Previously, several Mo complexes have been examined through a systematic DFT study. As an example, on the [MoO 2 (SAP)] complexes and different substitutions on ligand showed that the presence of OH group (on a specific position on the aldehyde part) [19] or NO 2 substituent (on aminophenol part) [20] on the ligand provoked higher activity. The presence of 3-and 4-methoxy groups on the ligand was studied several times with other Mo complexes [21].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Previously, several Mo complexes have been examined through a systematic DFT study. As an example, on the [MoO 2 (SAP)] complexes and different substitutions on ligand showed that the presence of OH group (on a specific position on the aldehyde part) [19] or NO 2 substituent (on aminophenol part) [20] on the ligand provoked higher activity. The presence of 3-and 4-methoxy groups on the ligand was studied several times with other Mo complexes [21].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Solvent‐free conditions are one aspect of green chemistry, which are reported for oxidation of primary alcohols to aldehydes 41,42 . Our research group have studied several [MoO 2 L] n (L = ONO, ONS ligands) type cis ‐dioxomolybdenum(VI) Schiff base complexes as catalysts in solvent‐free olefin epoxidation, observing high catalytic activity 24,43–45 . We have to point out that the solvent‐free condition here means organic solvent‐free condition with no further added organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chlorinated solvents such as dichloroethane (DCE), a highly toxic solvent, has to be avoided [ 15 ]. In the research group, the processes have been found to be active without organic solvent using complexes with tridentate ligands [ 16 , 17 , 18 , 19 , 20 ] or polyoxometalates (POMs) [ 21 , 22 , 23 ], giving a first step towards a cleaner process. The oxidant used in this case is tert -butyl hydroperoxide (TBHP) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%